Complete superior and inferior sagittal sinus thromboses with multiple cranial nerve pareses and transient ischemic attack - Case report - Topsakal, C; Cihangiroglu, M; Kaplan, M; Akdemir, I; Tiftikci, M (Japan Neurosurgical Soc, 2002)
A 27-year-old woman with headache and right peripheral facial nerve paresis persisting for over 25 days, and left hemiparesis for 2 days, which had all been gradually improving, was admitted to our hospital as she suddenly developed horizontal and vertical diplopia. She had right fourth and sixth cranial nerve pareses, papilledema, and right orbital venous congestion, and also experienced a seizure on the day of admission. Magnetic resonance (MR) imaging and MR venography revealed complete superior and inferior sagittal sinus thromboses and significant collateral venous channels, but no parenchymal lesion. Fourth and seventh cranial nerve pareses and the left herniparesis resolved completely within 2 days, but she concurrently developed an episode of right herniparesis, which lasted for 30 minutes. The patient recovered with medical therapy. MR venography showed recanalization of both sinuses. She was neurologically intact except for minimal right abducens nerve paresis at discharge, 40 days after admission. Multiple cranial nerve pareses with transient ischemic attack is an extremely rare manifestation of superior sagittal sinus thrombosis. Transient functional disturbance due to temporary reduction of tissue perfusion caused by overload of the collateral channels is more likely to be responsible for the transient ischemic attack and reversible ischemic neurological deficit.
Keywords: cranial nerve paresis; reversible ischemic neurological deficit; sagittal sinus; sinus thrombosis; transient ischemic attack